Efeitos da L-arginina na proteção renal por meio da dosagem plasmática e urinária de biomarcadores e histologia: estudo em modelo experimental de lesão de isquemia e reperfusão em ratos sob anestesia inalatória - Bussmann, André Roberto [UNESP] (2016)
Background: Nitric oxide (NO) inactivation occurs during renal ischaemia/reperfusion injury. This inactivation decreases endothelium-dependent and -independent arterial relaxation. Higher NO levels can improve endothelial dysfunction and arterial relaxation, thereby reducing the level of kidney injury. NO, synthesized from L-arginine by the enzyme nitric oxide synthase (NOS), seems to exerts a protective effect on the kidneys during tissue ischemia-reperfusion injury. The objective of this study was to evaluate the effect of L-arginine on the levels of injury biomarkers (pNGAL, uNGAL, KIM-1 e IL-18) for kidney function and histology in rats subjected ischaemiareperfusion injury. Methods: Thirty-two Wistar rats were randomised into the following 4 groups: Sham (S), laparotomy and right nephrectomy; Control (C), laparotomy and right nephrectomy and left kidney I/R; L-arginine control (LAC), laparotomy and right nephrectomy and L-arginine at a dose of 800 mg.kg-1 .dose-1 , 24 hours and 1 hour before surgery; and L-arginine (LA), laparotomy and right nephrectomy, left kidney I/R, and L-arginine at a dose of 800 mg.kg -1 .dose-1 , 24 hours and 1 hour before surgery. The pNGAL, uNGAL, KIM-1 e IL-18 and creatinine levels and kidney histopathology were analysed. The significance level was p < 0.05. Results: Creatinine was increased in all groups, with LA≈C>S≈LAC. pNGAL was increased in all groups and showed a similar trend. uNGAL levels were higher in groups C and LAC than LA and had intermediate values in group S. The KIM-1 levels were increased in the S, LAC and LA groups, but the contrast analysis revealed no differences between the groups in terms of their trends. IL-18 levels were higher in LA than in the other groups (C, S and LAC). The C and LA groups, compared with the S and LAC groups, had higher damage on the left side. There was no histopathological difference between C and LA or between S and LAC. Conclusion: L-arginine does not exert a damaging or protective effect on kidneys undergoing I/R injury based on the evaluation of kidney functions, histopathology and pNGAL and KIM-1 levels.